Smart distance measurement detector - Muhammad Rezduan, Othman (2012)
Distance measuring device is a device that is used to measure the length between two points or more. The distance measurement can be little bit difficult if the targets that want to be measured are far from reaching or high. The purpose of this project is to design and create a better distance better distance measurement that can encounter the measuring problem. An ultrasonic measuring device is proposed to solve the problem as the ultrasonic using an ultrasonic sound. The ultrasonic transducer is operating at frequencies in between 40 kHz to 250 kHz. The concept for the project is using the LCD screen and displayed the reading of distance measured and user can use switch button when measure value is taken. in the circuit, there have "Send", "Store", "Mask" and "Recall" switch. Besides that, the project using PlC 16F84A, which treated as the main component in hardware part, that can save up to 32 measurements, where the PlC will control the whole operation of the circuit while the measurement is executed.